AN INCLUSIVE ETHICS FOR THE TWENTY-FIRST CENTURY: IMPLICATIONS FOR STEM CELL RESEARCH - Kilner, John F. (Journal of religious ethics, 2009)
An important contribution of Christian ethics in the pluralistic world of the twenty-first century is to emphasize inclusivity. Rather than promoting the interests of certain groups at the expense of the most vulnerable, society does well to prioritize ways forward that benefit all. For stem cell research, inclusivity entails benefiting or at least protecting the beneficiaries of treatment, the sources of materials, and the subjects of research. Adult stem cells are already benefiting many ill patients without causing harm, and select adult cells may prove even more beneficial in the future. Other types of stem cells require other bodily materials such as eggs and somatic cells that should be obtained without unduly harming those who provide them. Research subjects, especially the most vulnerable, require protection as well. Should human embryos be included among them? Considerations of location, formation, individuation, and intention are here examined. Ultimately, for safety reasons as well as workability, pluripotency, and compatibility, relatively new types of pluripotent stem cells, especially induced pluripotent stem cells, warrant special priority according to an inclusive ethics.